2021
DOI: 10.1111/camh.12456
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the need of young people using online counselling services: how useful are standardised measures?

Abstract: Background Clinical assessments for children and young people entering a mental health service help to identify the prevalence of need within that population, support intervention recommendations, and enable service evaluation. Evidence related to the use of standardised measures in an ever‐expanding online environment, for the purpose of identifying need, is limited. Methods This study explores the reliability of using a standardised measure to detect clinical need in an online therapeutic environment, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Nomothetic PROMs are not always tested or designed with the digital mental health provision in mind, and they are often reported to be alienating by children and young people (Sharples et al, 2017). Furthermore, in an online therapeutic context, service users have been shown to score higher overall on nomothetic measures than the clinical population (Mindel et al, 2021).…”
Section: Digital Mental Health Accessmentioning
confidence: 99%
“…Nomothetic PROMs are not always tested or designed with the digital mental health provision in mind, and they are often reported to be alienating by children and young people (Sharples et al, 2017). Furthermore, in an online therapeutic context, service users have been shown to score higher overall on nomothetic measures than the clinical population (Mindel et al, 2021).…”
Section: Digital Mental Health Accessmentioning
confidence: 99%
“…While we're not able to confirm that every account of responses would be an honest one, our findings suggest that assessment data collected online is a true reflection of the individual's experiences of their need. This suggests that higher rates of need found within online populations are likely to be as a result of another online factor rather than over-catastrophe or exaggeration of response (Mindel et al, 2021). As demonstrated through the varying emotional states our participants recalled to have been in, it is unknown what emotional state an individual will present with when they come to register for, or use, an online service (Epstein & Klinkenberg, 2001).…”
Section: Motivations To Complete Online Assessmentsmentioning
confidence: 96%
“…Reliability of the data collected through online counselling services is central to supporting clinical practice and contributing to population-level data (Sharples et al, 2016). With the use of standardised mental health assessment measures indicating a greater level of need when collected online (Mindel et al, 2021), the question of reliability and validity of results is ever more crucial when considering the transference of measures validated in face-to-face (f2f) settings…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, for text‐based mental health interventions, regular human‐guided support has been shown to be more effective than machine or automatically guided content (Koelen et al, 2022) and their qualifications do not make them more efficacious as practitioners. Far less research was identified about the value of online interventions for young people in real‐world implementation or person‐centred approaches more broadly, perhaps owing to a lack of consistent measures or the delivery of this kind of support in online therapeutic environments (Mindel et al, 2021). For online and Internet‐delivered interventions the methodological tradition and preference for building an evidence base has been through experimental designs and Randomised Control Trials (RCT; Mohr et al, 2017).…”
Section: Introductionmentioning
confidence: 99%